PENGARUH MOTIVASI DAN EMOTIONAL INTELLIGENCE TERHADAP KINERJA GURU PADA LEMBAGA PENDIDIKAN NON-FORMAL DI WILAYAH TANGERANG, BANTEN - Bernard E Silaban (ESENSI: Jurnal Manajemen Bisnis, 2020)
The objective of the research is to see the significance influence of motivation and emotional intelligence toward the employee (teachers) performance at an Informal Education Institution in Tangerang Region, Banten. The sampling technique is saturative sampling with 40 fulltime teachers. The result of the research indicated that motivation and emotional intelligence have a significant impact toward the employee (teachers) performance, both simultaneously and partially. The other results also show that the teachers have good motivation, highly emotional intelligence and very good performance.